Chapter 2 Animal sacrifice on trial Moral reforms and religious freedom in India - Berti, Daniela (Taylor & Francis, 2024)
Animal sacrifices are commonly practised in Himachal Pradesh on various occasions, including public festivals at the district level. Over recent years criticism of the practice has increased and some cases have been brought before the court. This chapter focuses on three court cases that were jointly decided in 2014 by the Himachal Pradesh High Court, where the judge ruled a total ban on animal sacrifice in the state of Himachal Pradesh. The case is still pending at the Supreme Court which means that it may potentially have an impact at national level. I first consider the context of this controversy, and the official and unofficial discourses of those involved in the case. Based on the court file, newspapers and ethnographic data, I then analyse the judicial handling of the case, which refers to legal, ritual, or reformist arguments or to animal welfare. The last section draws a comparison with a case concerning animal sacrifice in the Santeria religion, decided by the U.S. Supreme Court, in order to bring out differences in the legal approaches in the two cases despite being both grounded in common law. It shows how, contrary to the legal handling of this issue in the Santeria case where the main concern is to protect religious freedom, in the Himachal Pradesh case the judge explicitly and repeatedly appealed to the role of the court in defining religion (as opposed to superstition), and to the court's responsibility in favouring 'moral progress' and promoting religious reforms.